Resposta anatômica e fisiológica de folhas de Ocotea odorifera (Vell.) Rohwer (Lauraceae) sob gradiente de estresse luminoso - Leme, Gabriele Marques (2015)
The potential for photosynthetic acclimation of plant species can be a determining factor in its occurrence and permanence in heterogeneous light environments. This study aimed to verify anatomical and physiological responses of Ocotea odorifera adults under different light regimes in order to verify their potential for acclimation. The data collection were carried out in forest fragments surrounded by pasture, in the city of Alfenas-MG. Gas exchanges of O. odorifera leaves (forest tree species shade tolerant) were analyzed in three distinct habitats with different irradiance conditions: the forest interior, the forest edge and the surrounding pasture matrix, and that leaves were distinguished in sun and shade leaves. Microclimatic data, such as air temperature, soil temperature and solar radiation, were measured to characterize the three environments. Analysis of anatomical and morphological variables from leaves were also realized. There was changes between the three environments and between the leaf types. Sun leaves exhibited higher values of photosynthesis, stomatal conductance, transpiration rate, stomatal density, abaxial and adaxial epidermis thickness, palisade parenchyma and total lamina thickness, than shade leaves. While the latter showed the highest values of intercellular carbon dioxide concentration, spongy parenchyma thickness and leaf area. The results indicate that O. odorifera individuals have high potential for photosynthetic acclimation in high light environments, since keeps high photosynthetic rates, even though the species is late secondary and shade tolerant.